Forming Entrepreneurial Intention of Students Through Entrepreneurship Education to Become Young Entrepreneurs - Aisha Alvia; Zuhrinal M Nawawi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The poverty and unemployment rate in Indonesia is quite high, the lack of jobs in Indonesia is one of the problems that must be overcome by the government. All kinds of ways have been done to help the community, one way that can be done is to change the mindset of the community from finding a job to an entrepreneur who opens jobs. This method needs to be done slowly and must be given an example. One of them is students, because students are drivers of change in a better direction, through knowledge of ideas, and skills that students have become locomotives of progress. Therefore the importance of this education can change the mindset of students from job seekers to entrepreneurs, this can help the government in solving this problem, therefore this entrepreneurial education is very important in building the characterization of students to become young entrepreneurs.